Elements of Leadership Style In The Leadership Construct Of Special Education Headmasters In Malaysia - et. al., Mohd Ali Masyhum bin Mohd Nor, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Special education leadership is leadership that requires a firm commitment from all parties involved. The commitment given must be based on the needs of students with special needs and also the welfare of teachers. Effective leadership in special education should make the management of special education better and ensure the harmony of every citizen. In addition, quality leadership also reflects the success of a special education program led. However, there are a handful of school leaders whose special education programs are not going well. This is due to several problems such as the knowledge of the leader, the experience of the leader, the attitude and also the leadership style practiced. These problems in turn affect the workload of special education teachers and their job satisfaction. This study details the leadership style factors in influencing the management course of special education programs.